PENGARUH STRUKTUR KEPEMILIKAN, PERILAKU MANAJEMEN LABA, FREE CASH FLOW HYPHOTESIS DAN ECONOMIC VALUE ADDED: PENDEKATAN PATH ANALYSIS1 - Wilopo Wilopo; Sekar Mayangsari (Journal of Indonesian Economy and Business (JIEB), 2002)
This paper investigates whether ownership structures, earnings management, growth opportunities, free cash flow hyphotesis are related to firm performance, as measured by economic value added. This paper use sample nonregulated companies during crisis period, 1998-2001. We find that during this period the management creates value. Our result also suggest that blockholders and free cash flow hyphotesis have indirect effects to economic value added through corporation policy, such as investing and financing. Interestingly, earnings management have direct effect to economic value added. These results imply that separation of management group ownership and control has significantly more negative relation to creating value in countries with low shareholders protection, as in emerging markets, whereas large blockholders have significantly more positive relation.Keywords: Ownership Structures, Earnings Management, Free Cash Flow Hyphotesis, Economic Value Added